2016
DOI: 10.33961/jecst.2016.7.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis with Various Amounts of Electrolyte in a Molten Carbonate Fuel Cell

Abstract: The effect of initial electrolyte loading (IEL) on cell performance in a coin-type molten carbonate fuel cell (MCFC) was investigated in this work. Since the material of MCFC depends on the manufacturer, optimisation requires experimental investigation. In total, four IEL values, 1.5, 2.0, 3.0, and 4.0 g, were used, corresponding to a pore filling ratio (PFR) of 38, 51, 77, and 102%, respectively. The cell performance with respect to the PFR was analysed via steady-state polarisation, step-chronopotentiomtery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The electrolyte occupies about 30% of the pore volume, which is a low value compared to the fraction determined by other authors (70%) . This apparent discrepancy can be explained by the fact that the multi‐modal pore sized cathode structure requires a lower fraction of electrolyte to infiltrate the entire material since larger pores, serving as gas channels, are not flooded by the electrolyte.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The electrolyte occupies about 30% of the pore volume, which is a low value compared to the fraction determined by other authors (70%) . This apparent discrepancy can be explained by the fact that the multi‐modal pore sized cathode structure requires a lower fraction of electrolyte to infiltrate the entire material since larger pores, serving as gas channels, are not flooded by the electrolyte.…”
Section: Resultsmentioning
confidence: 67%
“…The compromise between mass transport and specific surface area can be achieved by tailoring the pore size, since it determines the properties of open‐porous materials . Particularly, the variation of the pore size in the MCFC cathode material is providing two essential microstructure parameters: 1) the fraction of small pores formed after oxidation, which is responsible for capillary force based infiltration of the electrode with the electrolyte (in the range 15–30%), and 2) the enlarged internal surface area of pores (specific surface area). Summarizing, the specific surface area after oxidation should be as large as possible to form the longest possible TPB.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be said that the equations above can be used to calculate the remaining amount of electrolyte in the cell. In addition, it can be seen that the WRR performed with vacuum filtering is larger than that of the equation y = 0.13x -0.08, which was reported by the previous study [14]. This implies that the paper filtering method used in the previous experiment permitted reaction between moisture in the air and the carbonate electrolyte during filtering, which caused further reduction in the weight of the electrolyte.…”
Section: Wrr Wbd Wad -Wbd ---------------------------------100%mentioning
confidence: 62%
“…However, with 4 g electrolyte, the overpotential is increased largely because of an increase in the mass-transfer resistance caused by the thick layer of electrolyte formed on the surfaces of the electrodes. It was suggested that electrolyte conditions above 4 g caused flooding because excess electrolyte covered the electrode surface and pores [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation